Simulation of Groundwater Movement from Pits Fenced by Zchukovsky's Sprunts - N. Bereslavsky, E. (Journal of Water, 2021)
The hydrodynamic production considers the filtration of liquid from the pits, fenced with spools of Zhchukovskiy, through a layer of soil, underrunable by a well-permeable pressure aquifer, on the roof of which contains an impenetrable area. To study infiltration on the free surface of groundwater, a mixed regional multi-parametric task of the theory of analytical functions is formulated, which is solved by the Semibarinova-Kochina method and methods of conformal display of areas of special species characteristic of the tasks of underground hydromechanics. Refs. 24. Il. 4. Table 1.
Keywords: Filtration; Infiltration; Groundwater; Semibarinova-Kochina Method; Aquifer